Acute classroom exercise breaks improve on-task behavior in 4th and 5th grade students: A dose-response - Howie, Erin; Beets, M.; Pate, R. (Elsevier BV, 2014)
This study was the first to directly compare the acute effects of 5, 10, and 20 min of classroom exercise breaks on on-task behavior. Methods: In this within-subject experiment, 96 4th and 5th grade students, in 5 classroom groups, participated in each of four conditions: 10 min of sedentary classroom activity and 5, 10, 20 min of classroom exercise breaks led by research staff. On-task behavior was directly and systematically observed from videotapes before and after each condition. The post-test time-on-task scores were compared using a repeated measures mixed ANCOVA, adjusted for age, classroom, and the time-varying pre-test time-on-task. Results: Time-on-task was significantly higher in students after 10 min of classroom exercise breaks compared to a sedentary attention control (87.6% vs 77.1%, d = .45, p = .004). Conclusions: Ten minutes of classroom exercise breaks improved on-task behavior in children.